Sweet Treats and Savoury Bites - Khan, Hajra Maritta (Lahore Ferozsons (Pvt) Ltd., 2011)
This Book Presents a large variety of recipes for sweet and savoury snacks and salads.
Include Index, Glossary and Colored Illustrations.
Keywords: Sweet-Bites